All Power to the Party! The Sources of Ruling Party Strength in Authoritarian Regimes. Issue 1 (March 2021) - Zeng, Qingjie
Abstract: The role of political parties in facilitating authoritarian rule has been the subject of extensive research, but parties vary widely in their institutional strength to perform regime-bolstering functions. This article synthesizes existing literature to develop a general theory that explains the sources of ruling party strength in autocracies. We argue that party strength stems from a strategic calculation by political actors who weigh the benefits of building a strong party against its costs. The relative benefits of strong parties depend on the stage of the authoritarian life cycle and factors specific to the strategic environment. The observable implications of the theory are tested using a dataset that includes all autocratic ruling parties that were in power between 1940 and 2015. Consistent with our argument, parties that originated from revolutions tend to be the strongest, whereas those created to support an incumbent dictator tend to be the weakest. A country's resource endowments and external environment also shape the dynamics for party building.